2014
DOI: 10.1093/nar/gku847
|View full text |Cite
|
Sign up to set email alerts
|

SNP-guided identification of monoallelic DNA-methylation events from enrichment-based sequencing data

Abstract: Monoallelic gene expression is typically initiated early in the development of an organism. Dysregulation of monoallelic gene expression has already been linked to several non-Mendelian inherited genetic disorders. In humans, DNA-methylation is deemed to be an important regulator of monoallelic gene expression, but only few examples are known. One important reason is that current, cost-affordable truly genome-wide methods to assess DNA-methylation are based on sequencing post-enrichment. Here, we present a new… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 51 publications
2
5
0
Order By: Relevance
“…We replicated this observation in twelve biosamples (brain, blood, fallopian tube, fetal large and small intestine, hESCs, large airway epithelial cells, thyroid, muscle, epidermal keratinocytes, ovary, skin, and testis). These results are in agreement with recently reported findings from three genome-wide scale analyses of public RNA-Seq data [ 26 , 59 , 68 ]. These studies reported mean allele fractions showing either non-significant deviation (mean value = 0.504) [ 26 , 59 ] or significant deviation (average value ranging from 0.553 to 0.803) [ 26 , 68 ] for the WRB 3´-UTR rs1060180 and rs13230 SNPs.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We replicated this observation in twelve biosamples (brain, blood, fallopian tube, fetal large and small intestine, hESCs, large airway epithelial cells, thyroid, muscle, epidermal keratinocytes, ovary, skin, and testis). These results are in agreement with recently reported findings from three genome-wide scale analyses of public RNA-Seq data [ 26 , 59 , 68 ]. These studies reported mean allele fractions showing either non-significant deviation (mean value = 0.504) [ 26 , 59 ] or significant deviation (average value ranging from 0.553 to 0.803) [ 26 , 68 ] for the WRB 3´-UTR rs1060180 and rs13230 SNPs.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with recently reported findings from three genome-wide scale analyses of public RNA-Seq data [ 26 , 59 , 68 ]. These studies reported mean allele fractions showing either non-significant deviation (mean value = 0.504) [ 26 , 59 ] or significant deviation (average value ranging from 0.553 to 0.803) [ 26 , 68 ] for the WRB 3´-UTR rs1060180 and rs13230 SNPs. Furthermore, we provide evidence from 15 tissue repositories of allele rates that are consistent with the biallelic transcript expression of 10 genes that map to within 2-Mb around the WRB gene.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Contrasting previous genome-wide methods, no DNA genotyping data is required, as we solely rely on genotyping of RNA-seq data. The basic rationale is that in case of 100% imprinting, no heterozygous samples can be found in RNA-seq data, as they perfectly resemble homozygous samples (only a single allele is expressed) (see Methods section and Steyaert et al 30 ). The novel imprinting model describes the data for each SNP as a mixture of homozygous and heterozygous samples, more specifically as a mixture of genotype-dependent binomial distributions, with weights derived from Hardy–Weinberg equilibrium.…”
Section: Resultsmentioning
confidence: 99%